Il tema del merito di fronte ai problemi gravi dei nostri studenti in classe - Luigi D'Alonzo (Firenze University Press, 2022)
What worries and risks to become the problem of italian School for the near future is the social coexistence and which educational proposals favor the satisfaction of the needs of all students. The correct management of the class is, in fact, the fundamental condition in order to build our educational project aimed at supporting and enhancing the abilities of every student in the classroom.